ICT INTERVENTIONS IN INCLUSIVE EDUCATION - Jalajakumari, V T (SCHOOL SCIENCE, 2018)
The emergence of information communication technology in educational institutions made a fast change of pace in teaching-learning process as well as in the communication strategies among teachers, learners, parents, and other stakeholders in the society. It is proven fact that the innovative initiatives in ICT by industrialists and educationists ensure a paradigm shift from traditional monotonous way of educational transactions for special learners too to interesting and sustainably motivating learning habits. Most of the special learners today have been using smart phones, tablets and other digital game devices to play and learn since they could hold it. So it is justifiable and logical to align their learning process with their interesting digital play devices. Hence, along with the formal classroom learning, digital devices can also be supplemented with in-built provisions for guided and unguided practices, particularly among the differently abled learners. If paid more attention and policy support to develop e-contents, inclusive education can be imparted more effectively than ever. In the present paper, the author analyses and describes provisions in ICT to provide more effective educational supports for inclusive learners. A questionnaire was administered to the teachers of differently abled learners to identify the ICT provisions available and allotted for them and their impact on the education of differently abled learners. On the basis of the analysis of the questionnaire and the review done on the available provisions of ICT for special learners, the author tries to contribute some specific policy suggestions to improve the teaching-learning status of differently abled learners and at the same time suggests some innovative digital provisions of ICT for inclusive learners.